Funkcije in pomen intertekstualnih navezav v poeziji Uroša Zupana - Barbič, Nina (Primerjalna književnost, 2011)
This article provides an overview of Uroš Zupan's poetry collections with an emphasis on studying intertextual references and defining functions of the procedures used that make it possible to outline one of the aspects of Zupan's poetics and touch upon some key points of his poetic stance.
Keywords: Zupan, Uroš, 1963-; Slovene literature; slovenska književnost; slovenska poezija; 20.st.; medbesedilnost